Knowledge of breastfeeding among mothers in Public Antenatal Clinic, Malaysia. - Ibrahim, N.H.; Japar, S.; Ong, S.L.; Soh, K.G.; Soh, K.L. (2019)
A Baby-friendly Hospital Initiative (BFHI) has been launched since 1991. By 1998, Malaysia has been accredited as the third country of the world that fully applying BFHI in government hospital. The third step in BFHI is to discuss the importance and management of breastfeeding with all pregnant women and their families. The purpose of this study was to identify the knowledge of breastfeeding among antenatal mothers in public antenatal clinic, Malaysia prior to Prenatal Breastfeeding Talk. A cross-sectional study was used to collect data and descriptive analysis was used to figure the result. A total of 348 antenatal mothers were recruited in this study. Self-administered questionnaire was used which contain socio-demographic data, ten (10) questions on breastfeeding, the importance and confidence to breastfeed were asked. Furthermore, the feedback on effectiveness of method on giving education also been taken to identify best method in delivering education. Majority of participants (n=285, 81.9%) had scored more than half mark and being coded as good knowledge (1). In addition, majority of the participants (n=344, 98.9%) stated that they felt very confidence to breastfeed their baby. Prenatal Breastfeeding Talk provided in public clinic, Malaysia did had impact on maternal knowledge and confidence regarding breastfeeding.